ANALYSIS OF BIOMASS AND STORED CARBON STOCK IN MANGROVE FOREST AREA, TAMAN HUTAN RAYA NGURAH RAI BALI - Luh Putu Puspita Dewanti; Subagiyo Subagiyo; Diah Permata Wijayanti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2020)
Mangrove forests are transitional ecosystems between land and sea that occur mainly along tropical and subtropical coastlines. Ecologically, mangroves function as carbon sinks and stores, with most of them being allocated below the soil surface. It is possible that the increase in atmospheric CO2 that contributes to global warming can be reduced through the process of sequestration of carbon into the soil. The more carbon stored in the soil as soil organic carbon, it can reduce the amount of carbon in the atmosphere so that it can reduce global warming and climate change. SOC (Soil Organic Carbon) is distributed into various layers of soil, and its stability is also very diverse. The objectives of this research are:(1) Knowing the organic carbon storage below the soil surface in the mangrove forests of the Taman Hutan Raya Ngurah Rai and (2) Knowing the vertical variation of organic carbon stored in the soil in the mangrove forests of Taman Hutan Raya Ngurah Rai. The estimation of biomass using the method without harvesting by measuring diameter at breast height (DBH, 1.3 m) mangrove. Carbon deposits are estimated from 46% of biomass. The method used in this research is loss on ignition (LOI). The average distribution of soil organic carbon storage at a layer of 0 cm - 15 cm, 15 cm - 30 cm, 30 cm -50 cm, 50 cm -100 cm and > 100 cm respectively is 84.18 ton C / ha, 90 , 43 ton C / ha, 93.39 ton C / ha, 115.70 ton C / ha and 80.75 ton C / ha.